2003
DOI: 10.1148/radiol.2283020961
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced Digital Mammography: Initial Clinical Experience

Abstract: The results of this preliminary study suggest that contrast-enhanced digital mammography potentially may be useful in identification of lesions in the mammographically dense breast. Further investigation of contrast-enhanced digital mammography as a diagnostic tool for breast cancer is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(176 citation statements)
references
References 28 publications
6
166
0
4
Order By: Relevance
“…22 patients with suspect abnormalities found on conventional mammography or ultrasound [10]. The results showed the ability of temporal CEDM to show cancers and suggested a potential to identify cancers in dense breasts.…”
Section: Breast Tumoursmentioning
confidence: 83%
See 1 more Smart Citation
“…22 patients with suspect abnormalities found on conventional mammography or ultrasound [10]. The results showed the ability of temporal CEDM to show cancers and suggested a potential to identify cancers in dense breasts.…”
Section: Breast Tumoursmentioning
confidence: 83%
“…Clinical feasibility and initial experiences with CEDM have been reported for two techniques: temporal subtraction and dual energy [10][11][12][13]. Temporal subtraction CEDM involves a mask and a series of exposures, taken respectively before and after injection of contrast agent.…”
Section: Introductionmentioning
confidence: 99%
“…Jong, Yaffe and Skarpathiotakis, et al [6] presented their initial clinical experience with CEDM and believed that CEDM could potentially be useful in identifying lesions in the mammographically dense breast. Their paper was published in 2003, and they suggested that further investigation is certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Digital mammography, however, requires rigorous training for the radiologist and has a learning curve. The addition of intravenous contrast during digital mammography may help increase the detection rate of occult lesions in mammographically dense breasts [18].…”
Section: Screening Mammographymentioning
confidence: 99%
“…Positron emission tomography (PET) imaging after injection of radioactive tracer ( [18]F-fluorodeoxyglucose [FDG]) combines functional and anatomic imaging, which may enable improved cancer detection in dense breasts, improved differentiation of cancers from scar tissue, and improved definition of extent of disease prior to surgery. In a prospective, multicenter trial, PET imaging had 93% sensitivity and 83% specificity for index lesions (i.e., the lesions that prompted study entry) [40].…”
Section: Investigational Screening Modalitiesmentioning
confidence: 99%